Implementasi Metode Bermain Peran Dalam Mengenalkan Literasi Digital Pada Anak Usia Dini Di TK Ai-Anwar Sumber Sari Rek Kerrek - Leny Agustin Agustin; Musayyadah Musayyadah (Arfah BHMS Foundation, 2025)
This study aims to examine the implementation of role-playing methods in introducing digital literacy to early childhood students at TK Al-Anwar Sumber Sari Rek Kerrek, as well as to explore the resulting impacts. This research employed a descriptive qualitative approach to provide an in-depth portrayal of the role-playing process and its outcomes within the context of digital literacy. Data were collected through observation, interviews, and documentation. The data analysis used Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The findings revealed that the role-playing method was implemented systematically through three main stages: planning, execution, and evaluation. Children demonstrated high enthusiasm, began to recognize basic digital symbols and terms, and showed improvements in communication and social interaction skills. However, their understanding remained limited to imitation and required further guidance. As a solution, this study recommends that teachers consistently update digital learning media and provide contextual stimuli to help children fully understand the ethical use and function of technology. Furthermore, schools are encouraged to adopt role-playing methods integrated with digital literacy as an engaging and educational alternative to enhance digital competence from an early age.